Self-assembly of three-dimensional oxalate-bridged alkali(i)–lanthanide(iii) heterometal–organic frameworks. Issue 29 (9th July 2020) - Ponjan, Nutcha; Kielar, Filip; Dungkaew, Winya; Kongpatpanich, Kanokwan; Zenno, Hikaru; Hayami, Shinya; Sukwattanasinitt, Mongkol; Chainok, Kittipong
Abstract : Three isostructural 3D oxalate bridged alkali(i )–lanthanide(iii ) MOFs with a pcu net based on cubane-like [Ln4 O4 ] clusters and their magnetic, CO2 adsorption, and photoluminescence sensing properties are presented. Abstract : Three isostructural three-dimensional (3D) oxalate bridged alkali(i )–lanthanide(iii ) heterometal–organic frameworks with the general formula [Ln8 Na4 (ox)10 (μ3 -OH)8 ]·MeOH·10H2 O (Ln = Tb (1 ), Dy (2 ), Er (3 )) have been assembled from the solvothermal reactions of oxalic acid (H2 ox) with Ln(NO3 )3 and Na2 CO3 . These compounds crystallize in the tetragonal I 4/ m space group and exhibit a 3D six-connected uninodal net of pcu alpha-Po primitive cubic type based on tetranuclear [Ln4 (μ3 -OH)4 ] cubane clusters. Among them, compound 1 exhibits a multifunctional luminescent probe property for the detection of acetone, toluene, and Fe 3+ ions based on fluorescence quenching mechanisms. The magnetic investigations of 1–3 indicate antiferromagnetic coupling between the spin centers Ln 3+ ions. In addition, 1 and 3 show negligible adsorption capacity for carbon dioxide.